Effect of dyslexia on phonological awareness in children - Saeed, Diyar; Hajibadri, Zhirwan (Humanities Journal of University of Zakho, 2023)
Dyslexia is a genetic reading disorder that affects some children in different ways such as deleting sounds, replacing sounds and shortening sentences in reading. Dyslexia and phonology are correlated. The precise reception and production of language sounds facilitates the process of communication and reading successfully in an appropriate age in the learning process without any problems. This research paper titled the Effect of dyslexia on phonological awareness in children sheds light on dyslexia in children and its relationship to phonological and reading skills. When articulating sounds the syndrome is recognizable in the children with dyslexia. For the purpose of this study, data has been collected from children aged (8-14) years old (both genders) in the speech-language therapy center in Zakho. The researcher has applied a test made up of 7 steps for the purpose of identifying and searching for children who suffer from this syndrome but are unidentified among normal children. The study is based on descriptive theory and the data are analysed by SPSS program. The aim is to identify the number of children suffering from dyslexia in the participants based on the statistical findings. According to the test results, there is no difference among dyslexia samples and both genders are the same. This is due to the fact that these children are suppressed in schools and the teachers lack knowledge and management skills in the treatment of children suffering from dyslexia syndrome. There is a difference in reading skills where the rate was higher among male participants.